2019
DOI: 10.1177/1556984519836821
|View full text |Cite
|
Sign up to set email alerts
|

Early Discharge Does Not Increase Readmission Rates After Minimally Invasive Anatomic Lung Resection

Abstract: Objective Enhanced recovery pathways reduce length of stay and costs following lung resection. However, many fear that early discharge may lead to increased hospital readmissions. In this study, we aimed to determine whether early discharge was associated with increased readmission following anatomic lung resection. Methods Using the lung resection database approved by our institutional review board, we id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Forster et al also showed no difference in 30‐day readmission between patients discharged within 3 days and those discharged after 3 days in thoracoscopic anatomic lung cancer surgery 15 . Even among patients treated with the enhanced recovery pathway, Chevrollieret al concluded that discharge within 2 days after minimally invasive anatomic lung resection did not increase the risk of readmission 10 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Forster et al also showed no difference in 30‐day readmission between patients discharged within 3 days and those discharged after 3 days in thoracoscopic anatomic lung cancer surgery 15 . Even among patients treated with the enhanced recovery pathway, Chevrollieret al concluded that discharge within 2 days after minimally invasive anatomic lung resection did not increase the risk of readmission 10 …”
Section: Resultsmentioning
confidence: 99%
“…Early discharge has different definitions and criteria in various documents, without a specific minimum postoperative stay 8–11,15,16 . Currently, the most frequently used date of early discharge was 2 days or 1 day after surgery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of published studies have supported early discharge practice. Early discharge after lung cancer resection, 1,2 colorectal resections for benign and malignant disease, 35 and high-risk thoracic vascular operations 6 did not result in an increase in readmission rates. Similarly, early discharge was not associated with an increase in readmission among a generalized hepato-pancreato-biliary surgery weighted patient cohort.…”
mentioning
confidence: 88%